Academic Procrastination Among the Students in Thesis Writing - Haris, Andi Nadhirah Abd; Muliati, A.; Nur, Sahril (Interference: Journal of Language, Literature, and Linguistics, 2023)
Abstract. Academic Procrastination is a phenomenon of postponing work that rely on academician including college student. In terms of academic procrastination this research aims to explain academic procrastination phenomenon in final year student on their thesis writing that focus on to explain the tendency of academic procrastination and investigate the reason why the final year student tends to do academic procrastination. The participants of this research consist of 4 students from 12th semester and 4 students from 14th semester that can represent the final year student. This research used purposive sampling with semi structure interview, and it analyzed with qualitative method interactive cycle by Miles Huberman. The result showed that there is a tendency of academic procrastination in final year students, and the reason why the students do academic procrastination is divided into two branches such as internal and external. Internal factors include laziness, perfectionism, mentally unstable, social media addiction, and linguistic and conceptual factors. External factors include environment, other people's pressure, and family issues. Keywords: Academic Procrastination, Thesis Writing, Final Year Student